Psychological resilience, athletic experience, and competitive level of judokas. A transversal study - Garrido-Muñoz, María; Blanco-García, Cecilia; Diez-Vega, Ignacio; García-Merino, Sonia; Acebes-Sánchez, Jorge; Rodríguez-Romo, Gabriel (Frontiers in Psychology, 2024)
While there is agreement on the positive link between psychological resilience and athletic performance, conclusive findings regarding the association between psychological resilience and other variables of interest (for example, age, gender, type of sport or competitive level) remain elusive. Objective: The study aimed to assess psychological resilience levels among judokas and explore potential associations with demographic factors, judo experience and competitive level. Methods: A total of 702 judokas (469 men and 233 women) participated in the study, of whom 194 (27.6%) were classified as TOP by their competitive level. Psychological resilience was evaluated using the Spanish version of the 10 item Connor-Davidson Resilience Scale (CD-RISC 10), with a score range from 0 to 40. Independent T-test and Pearson's coefficient were used for bivariate analysis. A two-way non-parametric ANCOVA was carried out to analyse the impact of gender and competitive level on psychological resilience. Results: The judokas showed total mean scores in the CD-RISC 10 of 33.08 points (SD = 4.79), considered high. Levels of psychological resilience were significantly higher among men (33.36±4.76) than women (32.53±4.80) and were positively correlated with age and number of years practicing and competing in Judo (p = 0.019). Judokas with a higher competitive level (TOP judokas) showed significantly higher levels of resilience than the others (non-TOP judokas) (p < 0.001). These differences in resilience according to competitive level persisted, among both men and women, when adjusting the model of analysis (two-way ANCOVA) for all variables considered in the study, although with a small effect size. Conclusion: The results suggest that the practice of Judo, especially over long periods of time, is associated with high scores in psychological resilience. Furthermore, psychological resilience appears to be a differentiating variable among judokas at a high-competitive level, and its evaluation and development using different strategies based on age and gender should be considered by trainers and psychologists.